Fetal Alcohol Spectrum Disorders in a Rocky Mountain Region City: Child Characteristics, Maternal Risk Traits, and Prevalence. (15th April 2020) - May, Philip A.; Hasken, Julie M.; Bozeman, Rosemary; Jones, Jo‐Viviane; Burns, Mary Kay; Goodover, Joelene; Kalberg, Wendy O.; Buckley, David; Brooks, Marita; Ortega, Marian A.; Elliott, Amy J.; Hedrick, Dixie M.; et al.
Abstract : Objective: To document prevalence and traits of children with fetal alcohol spectrum disorders (FASD) and maternal risk factors in a Rocky Mountain city. Methods: Variations on active case ascertainment methods were used in 2 first‐grade cohorts in all city schools. The consent rate was 59.2%. Children were assessed for physical growth, dysmorphology, and neurobehavior and their mothers interviewed. Results: Thirty‐eight children were diagnosed with FASD and compared with 278 typically developing controls. Total dysmorphology scores summarized well the key physical indicators of FASD and defined specific diagnostic groups. On average, children with FASD performed significantly poorer than controls on intellectual, adaptive, learning, attention, and behavioral tasks. More mothers of children with FASD reported drinking prior to pregnancy and in the first and second trimesters, and had partners with drinking problems than mothers of controls; however, reports of comorbid alcohol use and 6 other drugs were similar for mothers of children with FASD and mothers of controls. Mothers of children with FASD were significantly younger at pregnancy, had lower average weight before pregnancy and less education, initiated prenatal clinic visits later, and reported more health problems (e.g., stomach ulcers and accidents). Children with FASD had significantly lower birth weight and more problems at birth, and were less likely to be living with biological mother and father. Controlling for other drug and tobacco use, a FASD diagnosis is 6.7 times (OR = 6.720, 95% CI = 1.6 to 28.0) more likely among children of women reporting prepregnancy drinking of 3 drinks per drinking day (DDD) and 7.6 times (OR = 7.590, 95% CI = 2.0 to 31.5) more likely at 5 DDD. Prevalence of FAS was 2.9–5.8 per 1, 000 children, and total FASD was 34.9 to 82.5 per 1, 000 children or 3.5 to 8.3% at this site. Conclusion: This site had the second highest prevalence of FASD of the 4 Collaboration on FASD Prevalence sites and clearly identifiable child and maternal risk traits. Abstract : The general cognitive abilities scores of children in the Rocky Mountain site were poorer among children with fetal alcohol spectrum disorders (FASD) than controls and poorest among children with alcohol‐related neurodevelopmental disorder (ARND). Mothers of children with FASD weighed less and sought prenatal care later during pregnancy than mothers of typically‐developing controls. High levels of self‐reported pre‐pregnancy drinking was strongly associated with children with FASD. This site had the third highest prevalence of FASD of the four Collaboration on Fetal Alcohol Spectrum Disorders Prevalence (CoFASP) sites, 3.5% to 8.3%.